Geographical variation in the chemical profile and antimicrobial activity of Solidago gigantea essential oils - Filep, Rita; Nagy, David U.; Ormai, Edit; Kocsis, Béla; Szilágyi-Utczás, Margita; Purger, Dragica; Balázs, Viktória Lilla (Frontiers in Microbiology, 2026)
IntroductionThe antibacterial significance of the essential oil of Solidago gigantea, a North American native species invasive in Europe, remains poorly understood. In this study, we investigated the chemical composition of Solidago gigantea essential oils (SEO) collected from three distinct Hungarian locations and evaluated their antibacterial activities against Escherichia coli ATCC 25922, methicillin-resistant Staphylococcus aureus (MRSA) ATCC 25923, and Pseudomonas aeruginosa ATCC 27853.MethodsEssential oils (SEO1, SEO2, SEO3) were obtained from inflorescences of Solidago gigantea by water-steam distillation. Chemical profiles were determined using gas chromatography–mass spectrometry (GC–MS). Antibacterial activity was assessed by broth microdilution, biofilm inhibition, and membrane damage assays, while scanning electron microscopy was used to visualize bacterial cell alterations.ResultsA total of 110 constituents were identified, and relative quantities of certain components varied among samples. The major components included cyclocolorenone (10.46–29.69%), α-pinene (5.09–12.41%), α-gurjunene (2.76–6.32%), and bornyl acetate (4.31–6.06%). Minimum inhibitory concentration tests revealed that E. coli was the most susceptible (0.31–0.62 mg/mL), MRSA showed intermediate sensitivity (0.62–1.25 mg/mL), and P. aeruginosa was the most resistant (1.25–2.50 mg/mL). Biofilm assays showed strong inhibitory effects: E. coli biofilms were reduced by up to 95.7%, MRSA by over 90%, and P. aeruginosa by 87.3%. Synergistic interactions were observed between SEO and gentamicin against P. aeruginosa, and between ceftriaxone and the oil against E. coli. The essential oil’s effectiveness varied by sampling location, with the SEO3 sample showing the strongest antimicrobial activity, including the highest biofilm inhibition and over 80% membrane disruption in all bacterial species after 60 min.ConclusionThe essential oil of Solidago gigantea showed antibacterial and biofilm-inhibitory activity, influenced by the plant’s geographical origin.